MANAJEMEN SISTEM INFORMASI AKADEMIK DALAM MENINGKATKAN KUALITAS LAYANAN ADMINISTRASI DI UNIVERSITAS NAHDLATUL ULAMA GORONTALO - Sri Ningsih Ratnasari Podomi; Abdurrahman R. Mala; Baso Tola (STKIP Pesisir Selatan, 2026)
Digital transformation in higher education requires universities to manage academic administrative services effectively, efficiently, and based on information technology. This study aims to analyze the management of Academic Information Systems (SIAKAD) in improving the quality of administrative services at Nahdlatul Ulama Gorontalo University. The research uses a qualitative approach with a case study type. Data was collected through observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model which included data condensation, data presentation, and conclusion drawn. The results of the study show that the management of the Academic Information System has been carried out through the functions of planning, organizing, implementing, and supervising. The implementation of SIAKAD makes a significant contribution to improving the quality of administrative services through accelerating access to information, increasing the effectiveness and efficiency of services, and strengthening transparency and accountability in academic management. However, the implementation of the system still faces several obstacles, including low digital literacy of users, limited technological infrastructure, and not optimal integration of academic data. The novelty of this research lies in the analysis of the management of the Academic Information System which not only focuses on the technical aspects of the system, but also on the aspects of governance, the readiness of human resources, and the transition process from manual to digital-based systems in improving the quality of administrative services in universities.